The Reception of Kadazandusun University Students towards the Kadazandusun Columns in Sabah's Local Newspapers - Andreas Totu; Halina Sendera Mohd Yakin (International Organization of Scientific Research (IOSR), 2014)
This paper aims at investigating the motivations that generate the interests of Kadazandusun students to read news from the Kadazandusun column in three local newspapers namely the Daily Express, The New Sabah Times and Borneo Post. This study also examines the newspaper reading habits among university students and explores what elements in the news that is able to gratify their reading needs. There are 140 respondents for this study that consist of students from Universiti Malaysia Sabah. The Uses and Gratifications Theory is used to explain the reading patterns among the respondents. Preliminary outcomes show that Kadazandusun students appear not interested to read the Kadazandusun language news because they are no longer proficient with the language and news that published in the column are available in the English and Malay versions. Respondents only visit the column to look for specific Kadazandusun terms or words. Some recommendations are put forward to improve the column in this study